Log(x-1)+log(x+1)=0

Simple and best practice solution for Log(x-1)+log(x+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Log(x-1)+log(x+1)=0 equation:


Simplifying
Log(x + -1) + log(x + 1) = 0

Reorder the terms:
goL(-1 + x) + log(x + 1) = 0
(-1 * goL + x * goL) + log(x + 1) = 0
(-1goL + goxL) + log(x + 1) = 0

Reorder the terms:
-1goL + goxL + glo(1 + x) = 0
-1goL + goxL + (1 * glo + x * glo) = 0
-1goL + goxL + (1glo + glox) = 0

Reorder the terms:
1glo + glox + -1goL + goxL = 0

Solving
1glo + glox + -1goL + goxL = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'go'.
go(l + lx + -1L + xL) = 0

Subproblem 1

Set the factor 'go' equal to zero and attempt to solve: Simplifying go = 0 Solving go = 0 Move all terms containing g to the left, all other terms to the right. Simplifying go = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(l + lx + -1L + xL)' equal to zero and attempt to solve: Simplifying l + lx + -1L + xL = 0 Reorder the terms: -1L + l + lx + xL = 0 Solving -1L + l + lx + xL = 0 Move all terms containing g to the left, all other terms to the right. Add 'L' to each side of the equation. -1L + l + lx + L + xL = 0 + L Reorder the terms: -1L + L + l + lx + xL = 0 + L Combine like terms: -1L + L = 0 0 + l + lx + xL = 0 + L l + lx + xL = 0 + L Remove the zero: l + lx + xL = L Add '-1l' to each side of the equation. l + lx + -1l + xL = L + -1l Reorder the terms: l + -1l + lx + xL = L + -1l Combine like terms: l + -1l = 0 0 + lx + xL = L + -1l lx + xL = L + -1l Add '-1lx' to each side of the equation. lx + -1lx + xL = L + -1l + -1lx Combine like terms: lx + -1lx = 0 0 + xL = L + -1l + -1lx xL = L + -1l + -1lx Add '-1xL' to each side of the equation. xL + -1xL = L + -1l + -1lx + -1xL Combine like terms: xL + -1xL = 0 0 = L + -1l + -1lx + -1xL Simplifying 0 = L + -1l + -1lx + -1xL The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 5(3x)=4 | | 9x=12x+1 | | -3x+32=5 | | 5x+1=4x+10 | | 3x+12=-80-10x | | 11x-7=10x+4 | | 15+3x=9+6x | | 5-(5y+8)=5y+3 | | sin(3x+pi)=0 | | -3(-2(-5)+2)+6(-5)-4(2)= | | 4x+3(2x-1)-4x=25 | | x^2+8x+15=8e | | -(8+10n)=6+4n | | 3s^3+16=4S^2+12S | | -4+5ln(10v+1)=1 | | 7(-3(-5)+2)-11(-5)+18= | | 10x-8(-1+7x)=8+3x | | 6r-70=-2 | | -5(x+5)=-25 | | 3s^3-4S^2-12S+16=0 | | 10x-143=2x-7 | | 4+6x=-21+x | | 1-2x-5x=-55 | | 4x+9+x=9 | | 0=x^2-8x-120 | | 9x+8y=-12 | | 27=3x+4x+6 | | 17=4y | | 9ln(6-9a)=36 | | 3(x-2)+15=-3(x-3)+3x | | 4(6x-8)=-4x+52 | | 2(5x-4)=10x |

Equations solver categories